2022
DOI: 10.1029/2021ef002396
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Historical Anthropogenic Soil Erosion in the Midwestern United States

Abstract: Conventional agricultural practices have accelerated soil erosion rates, resulting in widespread soil degradation throughout the world's agricultural regions (Montgomery, 2007b). Soil degradation diminishes soil fertility by removing organic matter and nutrients (Pimentel, 2006), which, without countervailing practices such as fertilization and genetic crop enhancements, leads to reductions in crop yields (Lal, 2004;Tilman et al., 2002). Fertilizer use, however, does not fully restore the productivity of erode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Our findings and those of others suggest there has been substantial burial of SOC within the Midwestern U.S. (Li et al., 2018; Papiernik et al., 2009; Smith et al., 2001; Young et al., 2014). Given that a large extent of the Midwestern U.S. has soils where SOC stocks have been degraded (Thaler et al., 2021, 2022), there is potential to restore agricultural soils via regenerative practices (Montgomery, 2017; Schneider et al., 2021). Whether adoption of no‐till farming can also return atmospheric SOC to soils is a matter of debate; field trials have shown that no‐till farming can increase SOC (Kumar et al., 2012; West & Post, 2002) and regionwide studies and compilations have shown that no‐till increases SOC in upper soil horizons (Christopher et al., 2009; Luo et al., 2010; Nunes et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings and those of others suggest there has been substantial burial of SOC within the Midwestern U.S. (Li et al., 2018; Papiernik et al., 2009; Smith et al., 2001; Young et al., 2014). Given that a large extent of the Midwestern U.S. has soils where SOC stocks have been degraded (Thaler et al., 2021, 2022), there is potential to restore agricultural soils via regenerative practices (Montgomery, 2017; Schneider et al., 2021). Whether adoption of no‐till farming can also return atmospheric SOC to soils is a matter of debate; field trials have shown that no‐till farming can increase SOC (Kumar et al., 2012; West & Post, 2002) and regionwide studies and compilations have shown that no‐till increases SOC in upper soil horizons (Christopher et al., 2009; Luo et al., 2010; Nunes et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of dynamic replacement in our model would increase the amount of eroded SOC because SOC concentration in the actively eroding areas would be partially replenished. However, dynamic replacement seems to play a small role compared to erosional SOC transport in the Midwestern U.S. because there is a widespread and persistent absence of A-horizon soils on the hilltops (Thaler et al, 2021(Thaler et al, , 2022, which indicates SOC loss via erosion far outpaces its replacement by crops. Additionally, Kwang, Thaler, Quirk, et al (2022) found that the spatial pattern of SOC erosion can be reproduced by soil transport dynamics alone, which is also consistent with SOC reduction via soil erosion greatly outpacing dynamic replacement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the USA, current intensive agricultural production has led to undesirable effects on the environment and a gradual decrease in land productivity (Kassam et al ., 2014; McDaniel et al ., 2014; Benitez et al ., 2017). The average soil loss over the last 100 yr of crop cultivation across the Midwest has been estimated to be 7.2 ± 4.8 Mg ha −1 yr −1 (Thaler et al, 2022). Historic and modern soil erosion reduces cropland productivity and agroecosystem resiliency.…”
Section: Introductionmentioning
confidence: 99%